Oro-mandibular manifestations of primary hyperparathyroidism - Sachin Rai; Sanjay K Bhadada; Vidya Rattan; Anil Bhansali; D S Rao; Viral Shah (Wolters Kluwer Medknow Publications, 2012)
Aims and Objective : To determine the effects of Primary Hyperparathyroidism on oral cavity in a symptomatic contemporary Indian population by taking note of the following parameters: (1) Radiological alteration of lamina dura, (2) mandibular cortical width, (3) prevalence of brown tumor, and (4) mandibular tori. Study Design : Twenty-six patients of Primary Hyperparathyroidism were examined clinically and radiologically for extra- and intraoral abnormalities. Loss of lamina dura, mandibular cortical width, presence of mandibular tori, and brown tumors were assessed and correlated with serum Calcium, Phosphate, Parathormone, and Alkaline phosphatase. The results were compared with twenty-six age- and gender-matched control subjects. The data was expressed as mean ± SD, and a probability (p) value of < 0.05 was considered significant. Pearson's statistical method was used to assess the significant correlation between radiological measurements and biochemical values. Results : Generalized absence of the lamina dura was the most consistent finding and there was a significant correlation between its loss and altered parathormone, alkaline phosphatase, and inorganic phosphate, but not with serum calcium or the duration of the disease. Mean values (in mm) for the cortical indices were significantly lower in the patients compared to the controls and correlated significantly with parathormone and alkaline phosphatase. None of the patients had mandibular tori and only one patient had a brown tumor. Conclusion : Loss of lamina dura, ground glass appearance, and mandibular cortical width reduction are common findings in primary hyperparathyroidism and these are significantly correlated with elevated parathormone and alkaline phosphatase. However, the presence of brown tumors and oral tori are less commonly encountered features.